Penerapan Media Digital dan Model Discovery Learning dalam Pembelajaran Menulis Teks Narasi di Sekolah Dasar - Purnawati, Feronica Dewi; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Jayapangus Press, 2025)
This study aims to describe the application, utilization, constraints, and learning solutions of writing narrative texts with digital media and discovery learning models. The method used is qualitative descriptive with a case study approach. The data is information about the application, utilization, constraints, and learning solutions for writing narrative texts with digital media and discovery learning models. Data sources were obtained from grade V students, teaching teachers, the learning process with an independent curriculum, and learning tool documents in the form of Learning Outcomes, Teaching Modules, and LKPD. Data was collected through observation, interviews, and documentation analysis. The research sample was conducted by purposive sampling with all students as research subjects. Data validity uses triangulation of sources and methods by comparing data obtained from various sources and different data collection methods. The data was analyzed using the interactive techniques of the Miles and Huberman model, with the stages of data collection, data reduction, and data presentation/verification. The study results show that (1) Integrating YouTube digital media with the discovery learning model is effective, with no misconceptions between teachers and students. (2) YouTube helps develop students’ narrative writing skills and boosts their motivation. (3) Challenges include limited school infrastructure, varying student readiness for digital media, and difficulties in independent exploration. (4) Solutions involve enhancing technology infrastructure, improving digital media skills, and offering independent writing training.